Brand Awareness Analysis of and Extensive Rural Reaching Capital Item: A Case Study in Kanyakumari District - Jebanesan, M. Jezer; Bhavani, S. (Indian Journal of Marketing, 2007)
In today's business environment companies can survive only if they can get, retain and add more customers by delivering appropriate products and services. They should be capable of creating an unbreakable lifetime relationship with customers. These companies should be able to reach the rural consumers, who are presently increasing becoming more comfortable in economic terms with increased purchasing power. Hence the strategies need to be more home-intrusive and neo-literate friendly.All organizations are trying to develop new models with novel additional features with a view of achieving these goals. Therefore the companies are sensitive to get the feedback on satisfaction levels and potentials of future expectations. The company also wants to find different means to improve the service facilities provided to their customers, especially from the rural areas.